Multicentric evaluation of BioFire FilmArray Pneumonia Panel for rapid bacteriological documentation of pneumonia. (September 2021) - Gastli, Nabil; Loubinoux, Julien; Daragon, Matthieu; Lavigne, Jean-Philippe; Saint-Sardos, Pierre; Pailhoriès, Hélène; Lemarié, Carole; Benmansour, Hanaa; d'Humières, Camille; Broutin, Lauranne; Dauwalder, Olivier; Levy, Michael; et al.
Abstract: Objectives: To evaluate performances of the rapid multiplex PCR assay BioFire FilmArray Pneumonia Panel (FA-PP) for detection of bacterial pathogens and antibiotic resistance genes in sputum, endotracheal aspirate (ETA) and bronchoalveolar lavage (BAL) specimens. Methods: This prospective observational study was conducted in 11 French university hospitals (July to December 2018) and assessed performance of FA-PP by comparison with routine conventional methods. Results: A total of 515 respiratory specimens were studied, including 58 sputa, 217 ETA and 240 BAL. The FA-PP detected at least one pathogen in 384 specimens, yielding an overall positivity rate of 74.6% (384/515). Of them, 353 (68.5%) specimens were positive for typical bacteria while eight atypical bacteria and 42 resistance genes were found. While identifying most bacterial pathogens isolated by culture (374/396, 94.4%), the FA-PP detected 294 additional species in 37.7% (194/515) of specimens. The FA-PP demonstrated positive percentage agreement and negative percentage agreement values of 94.4% (95% CI 91.7%–96.5%) and 96.0% (95% CI 95.5%–96.4%), respectively, when compared with culture. Of FA-PP false-negative results, 67.6% (46/68) corresponded to bacterial species not included in the panel. At the same semi-quantification level (in DNA copies/mL for FA-PP versus in CFU/mL for culture), the concordance rate was 43.4% (142/327) for culture-positive specimens with FA-PP reporting higher semi-quantification of ≥1 log10 in 48.6% (159/327) of cases. Interestingly, 90.1% of detected bacteria with ≥10 6 DNA copies/mL grew significantly in culture. Conclusions: FA-PP is a simple and rapid molecular test that could complement routine conventional methods for improvement of diagnosis accuracy of pneumonia.